2019
DOI: 10.1007/s12325-019-01171-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Choice of Spinal Versus General Anesthesia in Patients Undergoing Ambulatory Surgery: Results of a Multicenter Observational Study

Abstract: Introduction: Available short-acting intrathecal anesthetic agents (chloroprocaine and prilocaine) offer an alternative to general anesthesia for short-duration surgical procedures, especially ambulatory surgeries. Factors determining the choice of anesthesia for short-duration procedures have not been previously identified. Methods: This observational, prospective, multicenter, cohort study was conducted between July 2015 and July 2016, in 33 private or public hospitals performing ambulatory surgery. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…This may be linked to factors including requirement of systemic analgesia and ability to mobilise but this was not measured in this service evaluation. Furthermore, our service evaluation highlighted that surgeon preference rarely influenced anaesthetic choice, which matches findings from previous literature [17].…”
Section: Choice Of Anaesthesiasupporting
confidence: 86%
“…This may be linked to factors including requirement of systemic analgesia and ability to mobilise but this was not measured in this service evaluation. Furthermore, our service evaluation highlighted that surgeon preference rarely influenced anaesthetic choice, which matches findings from previous literature [17].…”
Section: Choice Of Anaesthesiasupporting
confidence: 86%
“…While our study found that there is no difference in early postoperative mortality between patients undergoing THA or PHA and receiving general or regional anesthesia, other studies have found there may be differences in other postoperative complications and outcomes. It has been reported that patients undergoing ambulatory orthopedic procedures under general anesthesia had a faster time to initial micturition and unassisted ambulation when compared with spinal anesthesia, which can be significant in our patient population that is undergoing hip surgery [ 21 ]. While the use of general anesthesia in patients undergoing THA has been associated with increased postoperative adverse complications such as stroke and cardiac arrest, it was not associated with longer postoperative hospital length of stay or 30-day readmissions, which suggests that patients may be at an immediately increased risk of adverse outcomes postoperatively, but that risk decreases rapidly over time, likely as the body recovers from the effects of the general anesthetic agent [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of complication associated with intubation as well as early recovery are its other advantages. 1 For spinal anesthesia in patients undergoing LSCS the most common anesthetic agent used is hyperbaric Bupivacaine (0.5%). It usually takes care of anesthetic requirements during LSCS and supplementation with other anesthetic drugs are usually not required with Bupivacaine.…”
Section: Introductionmentioning
confidence: 99%